Exploring Light Meson Resonances in Two-Pion Photoproduction: A Regge Formalism Analysis - Bibrzycki Łukasz; Hammoud Nadine; Mathieu Vincent; Perry Robert J.; Szczepaniak Adam P. (EPJ Web of Conferences, 2024)
In the domain of hadron spectroscopy, the investigation of meson resonances plays a pivotal role. This study focuses on the significance of twopion photoproduction as a prominent avenue for studying meson resonances in the ππ system. By employing the Regge formalism, our model incorporates the background contribution from the well-known “Deck Mechanism” and emphasizes the significant ρ(770) resonance, representing the P-wave contribution arising from pomeron and f2 exchanges. The model is extended by accounting for scalar mesons, namely σ, f0(980) and f0(1370), contributing to the S-wave behavior, as well as the tensor meson f2(1270) corresponding to the D-wave contributions, while also considering non-resonant P- and S-wave components. The model contains a number of free parameters, which are constrained from a global fit of the available experimental data for angular moments up to L = 2 for M = 0, …, 2. The fitted angular moments are compared with experimental data obtained from CLAS. The key physical insights gained from the model are summarized. Furthermore, we extract the t-dependence of the Regge amplitude residue function for the subdominant exchanges, shedding light on their contribution to the overall dynamics.